2021
DOI: 10.1542/peds.2020-038489
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Visits and Hospitalizations for Child Abuse During the COVID-19 Pandemic

Abstract: This is a prepublication version of an article that has undergone peer review and been accepted for publication but is not the final version of record. This paper may be cited using the DOI and date of access. This paper may contain information that has errors in facts, figures, and statements, and will be corrected in the final published version. The journal is providing an early version of this article to expedite access to this information. The American Academy of Pediatrics, the editors, and authors are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 5 publications
6
63
0
1
Order By: Relevance
“…For example, among children presenting to children's hospitals with billing codes for physical abuse, number of injuries, mortality, and a hospital utilization metric for severity of presentation were similar during and before COVID-19. 15 Specific assessment of a severe form of child abuse, abusive head trauma, also demonstrated decreased presentations without significant increases in several markers of clinical severity (eg, ventilator use). 17 Our results align with these administrative data.…”
Section: Discussionmentioning
confidence: 99%
“…For example, among children presenting to children's hospitals with billing codes for physical abuse, number of injuries, mortality, and a hospital utilization metric for severity of presentation were similar during and before COVID-19. 15 Specific assessment of a severe form of child abuse, abusive head trauma, also demonstrated decreased presentations without significant increases in several markers of clinical severity (eg, ventilator use). 17 Our results align with these administrative data.…”
Section: Discussionmentioning
confidence: 99%
“…While there is concern for under detection of child maltreatment cases ( Baron et al, 2020 ; Humphreys et al, 2020 ; Rapoport et al, 2021 ), data is mixed regarding the incidence of presentations and hospitalizations for child abuse. Some studies reported more severe cases of abusive injuries ( Sidpra et al, 2020 ) and/or increased hospitalizations ( Swedo et al, 2020 ), while others demonstrated decreases in hospitalizations for abusive head trauma ( Maassel et al, 2021 ) and in hospital encounters for physical abuse ( Kaiser et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 Additionally, some early studies found increases in child abuse during COVID-19, while others noted a decrease in the number of NAT cases seen compared to previous years. 9 , 10 , 11 , 12 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%